Back pain in adolescent idiopathic scoliosis: A comprehensive review. (April 2023) - An, Juhyung K; Berman, Daniel; Schulz, Jacob
Purpose: Adolescent idiopathic scoliosis (AIS) is a common spinal deformity that affects millions of children worldwide. A variety of treatment algorithms exist for patients based on radiographic parameters such as the Cobb angle and the Risser stage. However, there has been a growing focus on nonradiographic outcomes such as back pain, which can cause functional disability and reduced quality of life for patients. In spite of this, back pain in AIS is poorly characterized in the literature. We aimed to summarize various factors that may influence back pain in AIS and the impact of different treatment methods on pain reduction. Methods: A comprehensive systematic review was undertaken using the PubMed and Cochrane database. Keywords that were utilized and combined with "Adolescent Idiopathic Scoliosis" included, "back pain, " "treatment, " "biomechanics, " "biochemistry, " "epidemiology, " and "biopsychosocial." The literature was subsequently evaluated and deemed relevant or not relevant for inclusion. Results: A total of 93 articles were ultimately included in this review. A variety of contradictory literature was present for all sections related to epidemiology, underlying biomechanics and biochemistry, biopsychosocial factors, and treatment methodologies. Conclusion: Back pain in AIS is common but remains difficult to predict and treat. The literature pertaining to causative factors and treatment options is heterogeneous and inconclusive. Longer-term prospective studies combining biopsychosocial intervention in conjunction with existing curve correction techniques would be meaningful.